Antiretroviral treatment-induced dyslipidemia in HIV-infected patients is influenced by the APOC3-related rs10892151 polymorphism - Fernández-Sender Laura; Rodríguez-Gallego Esther; Beltrán-Debón Raúl; Rull Anna; Pardo-Reche Pedro; Alonso-Villaverde Carlos; Aragonès Gerard; Camps Jordi; Joven Jorge (BMC, 2011)
Abstract Background The recently observed association between the APOC3-related rs10892151 polymorphism and serum triglyceride levels has prompted us the possibility to explore whether this genetic variant may play a major role in human immunodeficiency virus (HIV)/antiretroviral therapy-induced dyslipidemia. Methods We determined the rs10892151 genotype distribution and serum apolipoprotein (apo) C-III concentration in a group of HIV-infected patients (n = 208) and in a group of age and sex-matched healthy volunteers (n = 200). Circulating lipid and lipoprotein levels were followed for 12 months after antiretroviral treatment initiation in the HIV-infected group. Results There were no significant variations in the frequency of the A allele between the healthy and HIV-infected groups (7.5 vs. 8.6%, respectively; p = 0.7); additionally, the A allele was not related to serum apo C-III concentration. However, among patients receiving protease inhibitor (PI) treatment, carriers of the A allele had significantly increased serum triglyceride (5.76 ± 2.54 mmol/L) and total cholesterol (6.63 ± 2.85 mmol/L) concentrations together with depressed levels of HDL-cholesterol (0.75 ± 0.3 mmol/L) when compared with patients not carrying the allele (2.43 ± 1.32, 5.2 ± 2.17 and 1.24 ± 0.4 mmol/L, respectively) at the end of the study. This effect was only evident for HDL-cholesterol concentration when patients were treated with non-nucleoside reverse transcriptase inhibitors (1.05 ± 0.4 vs. 1.28 ± 0.4 mmol/L). Conclusions The A allelic variant of the rs10892151 polymorphism is not associated with serum apo C-III concentration, but predisposes HIV-infected patients to less favorable lipid profile, particularly in those patients treated with PIs.